Scenario building: field manual - Meinert, Sascha (Brussels, 2014)
"It is a manual for people who want to know more about scenario-building and are considering setting up their own scenario project. It has been designed as a compact and easily accessible overview of the method of scenario building and the different steps entailed in the process."